No differences in support of thrombin generation by neonatal or adult platelets - Bernhard, H.; Rosenkranz, A.; Novak, M.; Leschnik, B.; Petritsch, M.; Rehak, T.; Köfeler, H.; Ulrich, D.; Muntean, W. (Hämostaseologie, 2009)
Newborns have, despite low clotting factors and poor in vitro platelet function, a well functioning hemostasis. The reason for this is still not completely clear. The aim of our study was to investigate whether phospholipids in neonatal platelets differ from those in adult platelets in their total amount, in their exposure on the platelet surface, and their effect on thrombin generation (TG). Methods: Clotting times of newborn and adult platelet-rich plasma were measured. Effect of newborn and adult platelets on TG was measured by means of CAT (calibrated automated thrombography). In addition, the effect of newborn and adult platelets with or without stimulation by ionophor on TG was measured in a purified prothrombinase complex. Phosphatidylserine-exposure (PS) of newborn and adult platelets was measured by flow cytometry of annexin V binding. The amount of phospholipids (PL) was determined by means of mass spectrometry. Results: Clotting times of platelet-rich plasma (PRP) of newborns stimulated with ionophor showed a significant lower reduction of clotting time than in adult PRP. No differences in the support of TG between neonatal and adult platelets were found in neonatal or adult plasma by means of CAT. In the purified system TG was increased by adding ionophor stimulated platelets but no difference was evident between stimulated newborn and adult platelets. Flow cytometric analysis showed no difference in annexin V binding between adult and newborn platelets. The results of mass spectrometry showed a very similar amount and pattern of PL of adult and newborns platelets. Conclusion: Our results do not provide any evidence that a different PL content or expression of neonatal platelets may alter TG in neonates.
Keywords: Newborns; phospholipids; thrombin generation